Four flows of communication in the new normal: An exploratory study of a hybrid working setup in Philippine advertising agencies - Cabase, Mariah Jemina Q. (Animo Repository, 2023)
Using the communicative constitution of organizations (CCO) (McPhee, 2015; McPhee & Zaug, 2000), this paper explored the different communicative changes in Philippine advertising agencies that shifted to a hybrid working setup. Specifically, it studied the changes in its four flows: 1) membership negotiation, 2) reflexive self-structuring, 3) activity coordination, and 4) institutional positioning. Semi-structured interviews were conducted with eighteen (18) employees in two advertising agencies chosen through convenience sampling. Thematic analysis was utilized for data analysis. Results showed there were indeed changes in the four flows of communication, and some changes also happened to overlap with one or more flows. This study may benefit advertising agencies that are now starting to transition their company fully into implementing a hybrid working setup.